2019
DOI: 10.3847/1538-4357/ab517c
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Third Stellar Population in the Milky Way’s Disk

Abstract: The Milky Way is a unique laboratory, where stellar properties can be measured and analyzed in detail. In particular, stars in the older populations encode information on the mechanisms that led to the formation of our Galaxy. In this article, we analyze the kinematics, spatial distribution, and chemistry of a large number of stars in the Solar Neighborhood, where all of the main Galactic components are well-represented. We find that the thick disk comprises two distinct and overlapping stellar populations, wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 61 publications
11
60
0
Order By: Relevance
“…>90% ends at [Fe/H]≈-2 dex. This is consistent with the MDF of the metal-weak thick disk (Beers et al 2014;Carollo et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…>90% ends at [Fe/H]≈-2 dex. This is consistent with the MDF of the metal-weak thick disk (Beers et al 2014;Carollo et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…However, DTG-10 and DTG-15 are rotating much faster around the Galactic center ( v φ +140 km s −1 ; J φ +1100 kpc km s −1 ) than DTG-27 ( v φ ≈ +70 km s −1 ; J φ ≈ +600 kpc km s −1 ). The rotational motions of DTG-10/15 are compatible with the value suggested for the MWTD (Carollo et al 2019;. Comparison with both Carollo et al (2014) and Beers et al (2014) also point to similarities in (E, J φ ), but the Galactic gravitational-potential model used by these authors is different from ours, so this should be taken with caution.…”
Section: New Prograde Groupssupporting
confidence: 77%
“…used the powerful combination of photometric metallicities and precision astrometric surveys to produce a "blueprint" of the known stellar populations in the disk and halo systems of the Galaxy. In the process, these authors confirmed the presence of a dynamically heated disk population, named the "Splashed Disk" (SD; Bonaca et al 2017;Di Matteo et al 2019;Belokurov et al 2020;Amarante et al 2020a,b), and demonstrated that the metal-weak thick disk (MWTD) is an independent structure from the canonical thick disk (see also Carollo et al 2019).…”
Section: Introductionmentioning
confidence: 86%
“…The evidence accumulated so far and discussed above suggests that we may have identified the reality of the proto-disk as the metal-weak (or "hot") thick disk (see also Carollo et al 2019), and that this was present more than 10 Gyr ago. It is interesting that relatively low eccentricity stars have survived as such the dynamical impact of a massive minor merger 24 , allowing this disk to be traced back to lower and lower metallicities as Figure 14 shows.…”
Section: Further Insights On the Early Disk From Chemistry And Dynamicsmentioning
confidence: 87%